THE FUTURE OF QUALITY AND QUALITY MANAGEMENT SYSTEMS - Y. P. Adler; V. L. Shper (Russian Journal of Economics and Law)
Objective: Discussing the gap between the ISO 9001 requirements and the trend of modern management development.Methods: abstract-logical, correlation analysis. Results: the authors analyzed the practice of quality management systems certification according to the requirements of the ISO 9001. The analysis has shown that this standard is not consistent with the trends of management in the 21 century, because it lacks orientation to person, systemic approach and understanding of variability. In addition, one of the key problems of the ISO 9001 is a considerable bureaucracy in the quality management systems certification. To substantiate the inconsistency of the standard to contemporary reality, the authors make an attempt to evaluate the impact of certification on the development indicators of countries and to determine the need for such certification.To conduct the assessment, we analyze the dynamics of the number of the issued certificates in terms of countries and industries. Basing on the analysis, we come to the conclusion about the permanent reduction in the growth rate of the number of certificates. Then we make the correlation analysis between the number of the issued certificates and the number of indicators of socio-economic development in the same countries, such as GDP, education level index, corruption perception index, etc. The result was the conclusion about the absence of a significant relationship between these indicators; thus, we consider it inappropriate to continue the certification of quality management systems to comply with the ISO 9001 requirements. In conclusion we set out proposals for the way out of the situation.Scientific novelty: the use of economic-mathematical methods to justify the rejection of further certification according to ISO 9001. Practical significance: the conclusions formulated by the authors can be used in practical activities of organizations when deciding about the need for certification in accordance with ISO 9001 or rejection of such certification.